Identity and Diversity in the Hudoq Dance: A Review of Religious Moderation Based on Ancestral Heritage Among the Dayak Tribe - Robbaniyah, Nur; MJ, Noer Hidayat; Ningrum, Velida Apria; Ulya, Nur Afina (An-Nida', 2023)
The study of culture in the Dayak Wehea community continues to evolve, but various studies often overlook an examination of the religious identity displayed. This religious identity becomes a practice of religious moderation born in the Dayak Wehea community. Therefore, the author investigates how religious moderation is displayed through the identity and symbols contained in the Hudoq dance in the Dayak Wehea community. This article aims to discuss the Hudoq dance as one form of identity and heritage-based diversity in the Dayak Wehea tribe, particularly in the context of examining religious moderation. The Hudoq dance is not only an ethnic identity but also an ancestral heritage, serving as a religious practice in the community. This research combines field and literature studies, collecting data through interviews, documentation, and relevant literature. The data is discussed using a descriptive-analytical method with a qualitative approach. The article concludes that the practice of religious moderation in the Dayak Wehea community can be observed through the religious values displayed in the Hudoq dance. These religious values include the principles of unity, peace, tolerance among religious communities, and the balance between humans and the universe. The religious values presented in the rice harvest festival and the Hudoq dance contribute to the creation of unity and harmony in the Dayak Wehea community and its surroundings. Abstrak: Kajian tentang kebudayaan di masyarakat Dayak Wehea terus mengalami perkembangan namun berbagai kajian yang ada luput mengkaji identitas keberagamaan yang ditampilkan. Identitas keberagamaan ini menjadi praktik moderasi beragama yang dilahirkan di masyarakat Dayak Wehea. Oleh karena itu penulis meneliti bagaimana moderasi beragama ditampilkan melalui identitas dan simbol yang terkandung dalam tarian Hudoq di masyarakat Dayak Wehea. Artikel ini bertujuan mendiskusikan tentang tarian Hudoq, sebagai salah satu bentuk identitas dan keragaman berbasis warisan leluhur pada suku Dayak Wehea, khususnya dalam meninjau moderasi beragama. Tari Hudoq merupakan tari yang tidak hanya menjadi identitas kesukuan sekaligus warisan leluhur, tetapi juga menjadi praktik keagamaan di masyarakat. Penelitian ini dilakukan dengan jenis penelitian lapangan dan pustaka sekaligus, sehingga data dikumpulkan melalui wawancara, dokumentasi, serta literatur-literatur terkait topik kajian. Data-data tersebut didiskusikan dengan menggunakan metode deskriptis-analitis dengan pendekatan kualitatif. Artikel ini menyimpulkan bahwa pengamalan moderasi beragama yang berkembang di masyarakat Dayak Wehea dilihat melalui nilai-nilai keagamaan yang ditampilkan dalam tari Hudoq. Nilai-nilai keagamaan ini meliputi nilai persatuan, perdamaian, toleransi antar umat beragama, dan nilai keseimbangan antara manusia dengan alam semesta. Nilai-nilai agama yang ditampilkan pada kegiatan pesta padi dan tari Hudoq menjadi salah satu faktor pendorong terciptanya persatuan dan kesatuan di lingkungan masyarakat Dayak Wehea dan sekitarnya.